2014
DOI: 10.1016/j.jaci.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Somatic reversion in dedicator of cytokinesis 8 immunodeficiency modulates disease phenotype

Abstract: Background Autosomal recessive, loss-of-function mutations in DOCK8 cause a combined immunodeficiency characterized by atopy, recurrent infections, and cancer susceptibility. A genotype-phenotype explanation for the variable disease expression is lacking. Objective We investigated whether reversions contributed to the variable disease expression. Methods Patients followed at the NIH Clinical Center were studied. We performed detailed genetic analyses and intracellular flow cytometry to detect DOCK8 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 28 publications
(46 reference statements)
2
84
1
1
Order By: Relevance
“…However, a possible somatic reversion of the germline mutation may be present. 22 Eventually, genes mutated in the DOCK8-sufficient patients, such as PGM3 , 79 will be identified, and the diagnostic sequencing strategy can be expanded to include more genes (see the Online Repository for exclusion of other candidate genes in some of our families that do not have mutations in either DOCK8 or PGM3 ). In addition, a recent report 22 has demonstrated that in some patients DOCK8 gene expression can be reestablished in one or more subsets of cells through somatic reversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a possible somatic reversion of the germline mutation may be present. 22 Eventually, genes mutated in the DOCK8-sufficient patients, such as PGM3 , 79 will be identified, and the diagnostic sequencing strategy can be expanded to include more genes (see the Online Repository for exclusion of other candidate genes in some of our families that do not have mutations in either DOCK8 or PGM3 ). In addition, a recent report 22 has demonstrated that in some patients DOCK8 gene expression can be reestablished in one or more subsets of cells through somatic reversion.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequence analysis of selected cell populations can also uncover somatic mutations (SM) such as FAS gene mutations that are present in a subpopulation of CD4-, CD8- T cells but not in the germline of certain autoimmune lymphoproliferative syndrome (ALPS) patients (23). Somatic reversion can also ameliorate disease phenotype by “correcting” the genetic defect in appropriate cell lineages (24). …”
Section: Approaches To Study the Genetic Contribution To Diseasementioning
confidence: 99%
“…However, these viruses can reemerge from latency to cause disease in up to 30% of the population (Higgins et al, 1993;Kilkenny and Marks, 1996;Harpaz et al, 2008). In contrast to normal individuals, DOCK8-deficient patients with autosomalrecessive loss-of-function mutations in DOCK8 have impaired cellular and humoral immunity (Engelhardt et al, 2009;Zhang et al, 2009;Su et al, 2011;Jing et al, 2014) that manifests as extreme susceptibility to skin and other infections (Chu et al, 2012). Patients often suffer from disseminated and persistent viral skin infections including those caused by HSV, varicella-zoster virus, human papillomavirus, and molluscum contagiosum.…”
mentioning
confidence: 99%